Chromium(III) Removal from Wastewaters by a Weakly Acidic Resin Containing Carboxylic Groups - S. Kocaoba; G. Akcin (Adsorption Science & Technology)
As a conservative technology, ion exchange allows the removal and recycling of metals from liquid effluents. A process was applied for the removal of chromium(III) from wastewaters by ion exchange. This process was based on a weakly acidic cation-exchange resin (Amberlite IRC 86) capable of removing chromium(III) from the effluent, followed by selective separation and recovery during a regeneration procedure. Because of the difficult regeneration behaviour of the metal form of the carboxylate resin, special emphasis was given to the regeneration step of the resin where most of the practical problems were found. Five different regeneration procedures were adopted: elution with 1 M NaOH; elution with 1 M H 2 SO 4 ; elution with 1 M NaOH followed by 1 M H 2 SO 4 or vice versa; elution with NaOH followed by 1 M H 2 SO 4 /Na 2 SO 4 solution; and elution with alkaline H 2 O 2 /NaOH solutions followed by 1 M H 2 SO 4 . A non-conventional regenerant solution such as hydrogen peroxide in an alkaline medium seemed very promising. The anionic species formed (chromate) was eluted quantitatively from the cation-exchange resin and separated. The regeneration efficiency of chromium(III) was 89.5%. Influent chromium concentrations employed during the tanning process used in the leather industry were also considered. For this purpose, influent concentrations in the range 60–100 mg/l, service flow rates of 10 and 20 l/h and appropriate retention times were selected and experiments undertaken in a column system. The exhaustion step was carried out at 250 l/h with the recovery of chromium being 95.6%. The ion-exchange capacity of Amberlite IRC 86 was found to be 1.28 equiv/l. This study undertaken under laboratory conditions demonstrated that Amberlite IRC 86 resin was suitable for the removal of chromium(III) from wastewater.